Expression of the Pseudomonas aeruginosa PAK pilin gene in Escherichia coli. - Finlay, B B (1986)
Pseudomonas aeruginosa is a piliated opportunistic pathogen. We have recently reported the cloning of the structural gene for the pilus protein, pilin, from P. aeruginosa PAK (B. L. Pasloske, B. B. Finlay, and W. Paranchych, FEBS Lett. 183:408-412, 1985), and in this paper we present evidence that this chimera (pBP001) expresses P. aeruginosa PAK pilin in Escherichia coli independent of a vector promoter. The strength of the promoter for the PAK pilin gene was assayed, and the cellular location of the pilin protein within E. coli was examined. This protein was present mainly in the inner membrane fraction both with and without its six-amino-acid leader sequence, but it was not assembled into pili.